DEVELOPMENT AND APPLICATION OF A COMPUTER PROGRAM FOR FOUR-BAR LINKAGE AND SLIDER-CRANK MECHANISMS - OLADEJO KOLAWOLE ADESOLA; ADEKUNLE NURUDEEN OLATUNDE; ADETAN DARE; ABU RAHAMAN; ORIOLOWO KOLAWOLE TAOFIK (Journal of Engineering Studies and Research)
Complex mathematical problems have been solved with the aid of software application to obtain reliable results. The positional kinematic analysis of a slider crank mechanism involves computation of the motion parameters: linear displacement, velocity and acceleration of the slider; and angular velocity and angular acceleration of the connecting rod for every 300 variation of the crank angle. This study aimed to develop a customized software which can be used to efficiently analyse a given design of a four-bar and a slider-crank mechanisms. A program was written using VB (Visual Basic) programming language for the equations of angular velocities and angular acceleration of the coupler and follower for the four-bar linkage and the linear velocity and acceleration of the piston for the slider crank mechanism. The program was tested with different parameters for the mechanisms and the solutions compared with the results from manual calculations. The findings revealed that there were no differences (p ≤ 0.05) between the results using the program and manual calculations, which imply the accuracy of the program. It can be concluded that the program could be used to solve problems of four- bar linkage and slider-crank mechanisms.